Modification of granular activated carbon using low molecular weight polymer for enhanced removal of Cu2+ from aqueous solution - Yin, C.Y.; Aroua, Mohamed Kheireddine; Daud, Wan Mohd Ashri Wan (IWA Publishing, 2007)
Palm shell activated carbon was modified via surface impregnation with polyethyleneimine ( PEI) to enhance removal of Cu2+ from aqueous solution in this study. The effect of PEI modification on batch adsorption of Cu2+ as well as the equilibrium behavior of adsorption of metal ions on activated carbon were investigated. PEI modification clearly increased the Cu2+ adsorption capacities by 68 and 75.86 for initial solution pH of 3 and 5 respectively. The adsorption data of Cu2+ on both virgin and PEI-modified AC for both initial solution pH of 3 and 5 fitted the Langmuir and Redlich-Peterson isotherms considerably better than the Freundlich isotherm.